FILOSOFI EKONOMI ISLAM DAN IMPLEMENTASINYA DALAM PERBANKAN SYARIAH: PERSPEKTIF MASYARAKAT UMUM - Nazlah Yuningsih (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Islamic economics is a system of economics based on the values and principles of Islam. This system aims to achieve the welfare of society in general, both materially and spiritually. Islamic banking is one of the instruments of Islamic economics that plays an important role in achieving this goal. This study aims to examine the philosophy of Islamic economics and its implementation in Islamic banking from the perspective of the general public. This study uses a qualitative method with interviews as a data collection technique. The results of the study show that the general public understands that Islamic banking has a different philosophy than conventional banking. The general public also understands that Islamic banking applies Islamic principles in its operations, such as the principles of justice, equality, and prudence. This study concludes that the philosophy of Islamic economics and its implementation in Islamic banking have the potential to be accepted by the general public. This is because the philosophy and principles of Islam that underlie it are in line with the universal values that are believed by the general public.